Citrate 4% versus Heparin and the Reduction of Thrombosis Study (CHARTS) - MacRae, Jennifer M. (American Society of Nephrology, 2008)
Background and objectives: Citrate 4% has antithrombotic and antibacterial properties, which makes it a potentially superior alternative to heparin as an indwelling intraluminal locking agent. Design, setting, participants, and measurements: Sixty-one prevalent hemodialysis (HD) patients dialyzing with a tunneled cuffed HD catheter were randomized in a pilot study to receive either heparin 5000 U/ml or citrate 4% as a locking agent after HD. The primary outcomes were the development of catheter dysfunction (defined as a blood pump speed <250 ml/min or the use of tissue plasminogen activator) and catheter-associated bacteremia. The secondary outcomes were the development of an exit-site infection or bleeding complications (either local or systemic). Results: Citrate had comparable catheter dysfunction episodes to heparin (13/32 [41%] cases versus 12/29 [41%] cases, respectively). There were no differences in the development of catheter-associated bacteremia (2.2/1000 catheter days citrate versus 3.3/1000 catheter days heparin group; P = 0.607) or exit-site infection (2.2/1000 catheter days for both groups). Conclusions: The preliminary findings from our pilot study demonstrate that 4% citrate is effective in maintaining catheter patency and does not appear to have any increased incidence of infections. Because citrate is significantly cheaper and has a more favorable side effect profile than heparin, it can be considered a potentially better locking agent in HD catheters.